Husband and Wife Role to Maintain Family Resilience during the Covid-19 Pandemic: Islamic Law Compilation Perspective - Awaliyah, Dita Faradila; Al Farisi, Firman; Nadhiroh, Jamilatun; Musyafaah, Nur Lailatul (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2023)
During the Covid-19 Pandemic, many couples divorced due to various factors, including disputes and the economy. However, many families have strong resilience in the face of the Covid -19 Pandemic so that their families remain harmonious. This article discusses the role of husband and wife in improving family resilience during the Covid-19 Pandemic. This is field research was conducted in Medali, Mojokerto, East Java, Indonesia. The data is collected through interviews and documentation to answer existing problems. Qualitative methods with a deductive mindset analyze the results of interviews and documentation. This study concluded that during Covid-19 Pandemic, the husband and wife in Medali maintained their family resilience by playing a role in meeting daily needs, fulfilling economic aspects, and fulfilling education for children. In addition, they support each other and are convinced that this Pandemic is a provision from Allah, so they must pray and be grateful. The family carries out the role of husband and wife in Medali during the Covid-19 Pandemic according to the Compilation of Islamic law, articles 77 and 79.